Table of Content - - (Journal of engineering sciences and information technology, 2023)
Table of Content: 1. Enhancing The Performance of WDM-PDM 16-QAM Dr. Raghad Mohammad Fayez Alalfi, Dr. Abdulkareem Alsalem 2. Effect of window width on the fire speed spread in high-rise buildings Eng. Raya Haqqi Ismail, Dr. Omar Hazim Kharufa 3. Effect of Electromagnetic Field (ELF) on Humanʹs Body-Review Asst- Lecturer Ahmed Mohammed Farhan, Asst- Lecturer Hadeer Mohammed Farhan 4. An Efficient Energy Optimization Method for 5G Networks using Integrated Optimization Algorithm Eng. Wesam Ahmad Jaradat 5. The Preferences of Interior Design of the Middle-Class Families in Jordan Dr. Wafa Moh’d Fawaz Sinan, Prof. Demet Irkli Eryildiz